39th AIAA Fluid Dynamics Conference 2009
DOI: 10.2514/6.2009-4055
|View full text |Cite
|
Sign up to set email alerts
|

Aerothermodynamic Characteristics of Boundary Layer Transition and Trip Effectiveness of the HIFiRE Flight 5 Vehicle

Abstract: The heat transfer rate was measured using global phosphor thermography and the resulting images and heat transfer rate distributions were used to infer the state of the boundary layer on the windside, leeside and side surfaces. Boundary layer trips were used to force the boundary layer turbulent, and a study was conducted to determine the effectiveness of the trips with various heights. The experimental data highlighted in this test report were used determine the allowable roughness height for both the windsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…During descent, latest (highest Reynolds number) leading edge transition occurred when the diameter Reynolds number at the most upstream joint was 1. The minor axis (centerline) transitioned at a lower Reynolds number than the leading edge, which is consistent with prior CFD 69,70 and wind tunnel measurements 53,65 at hypersonic conditions that indicated that the centerline is more unstable and prone to lower Reynolds number transition. Centerline transition also showed a more gradual progression over time than the leading edge transition.…”
Section: Transition Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…During descent, latest (highest Reynolds number) leading edge transition occurred when the diameter Reynolds number at the most upstream joint was 1. The minor axis (centerline) transitioned at a lower Reynolds number than the leading edge, which is consistent with prior CFD 69,70 and wind tunnel measurements 53,65 at hypersonic conditions that indicated that the centerline is more unstable and prone to lower Reynolds number transition. Centerline transition also showed a more gradual progression over time than the leading edge transition.…”
Section: Transition Resultssupporting
confidence: 77%
“…Prior tests in the NASA Langley 20-inch Mach 6 wind tunnel demonstrated that roughness-induced transition from these fasteners would not propagate to the instrumented side of the payload. 65 The primary aerothermal instrumentation for HIFiRE-5 consisted of Medtherm Corporation coaxial thermocouples. Type T (copper-constantan) thermocouples were installed in aluminum portions of the aeroshell and Type E (chromel-constantan) were installed in the steel portions.…”
Section: Vehicle Descriptionmentioning
confidence: 99%
“…Roughness was applied using 2D (tape strips) and 3D (tape squares) to the HIFiRE-5 model leading edge in the NASA LaRC 20-inch Mach 6 wind tunnel. 33 Heat transfer measurements from these experiments were used to determine the transition location due to the roughness elements. The procedure to determine the transition location was similar to that outlined previously for smooth-body transition.…”
Section: A Discrete Roughness Correlations For the Frustummentioning
confidence: 99%
“…Figure 10 shows centerline transition Reynolds numbers derived from NASA LaRC Mach 6 wind tunnel heat transfer data. 33 The transition Reynolds numbers were extracted by plotting measured heat transfer rates in log-log coordinates. A straight line was fit to the sensibly laminar portion of the data, and another to the transitional portion of the data.…”
Section: Figure 7 Hifire-5 Reynolds Number and Mach Profilementioning
confidence: 99%
“…The follow-on effort under this ongoing analysis is focused on more thorough application of higher fidelity analysis tools and a deeper investigation of instability physics using numerical computations pertaining to both natural transition (see, for instance, Fig. 6.1) and the effect of boundary layer trips [44]. …”
mentioning
confidence: 99%